Gender difference in acquired seizure susceptibility in adult rats after early complex febrile seizures - Dai, Yun-Jian; Xu, Zheng-Hao; Feng, Bo; Xu, Ceng-Lin; Zhao, Hua-Wei; Wu, Deng-Chang; Hu, Wei-Wei; Chen, Zhong (Neuroscience bulletin, 2014)
Gender differences are involved in many neurological disorders including epilepsy. However, little is known about the effect of gender difference on the risk of epilepsy in adults with a specific early pathological state such as complex febrile seizures（FSs） in infancy. Here we used a well-established complex FS model in rats and showed that：（1） the susceptibility to seizures induced by hyperthermia, pentylenetetrazol（PTZ）, and maximal electroshock（MES） was similar in male and female rat pups, while males were more susceptible to PTZ- and MES-induced seizures than age-matched females in normal adult rats;（2） adult rats with complex FSs in infancy acquired higher seizure susceptibility than normal rats; importantly, female FS rats were more susceptible to PTZ and MES than male FS rats; and（3） the protein expression of interleukin-1β, an infl ammatory factor associated with seizure susceptibility, was higher in adult FS females than in males, which may reflect a gender-difference phenomenon of seizure susceptibility. Our results provide direct evidence that the acquired seizure susceptibility after complex FSs is gender-dependent.